THE IMPACT OF LEARNING ARABIC ON THE TOURISM INDUSTRY IN UZBEKISTAN - O‘tkirova , Latofat Sur’at qizi (GOLDEN BRAIN, 2024)
This article examines the influence of learning the Arabic language on the tourism sector in Uzbekistan. It explores how Arabic language proficiency plays a crucial role in enhancing communication between tourists and professionals in the tourism industry. The integration of Arabic language education into the curriculum for tourism-related programs and its impact on attracting Arab tourists, improving customer service, and facilitating international relations are discussed in this study.